2019
DOI: 10.1186/s12915-019-0688-7
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomes and metatranscriptomes shed new light on the microbial-mediated sulfur cycle in a Siberian soda lake

Abstract: Background The planetary sulfur cycle is a complex web of chemical reactions that can be microbial-mediated or can occur spontaneously in the environment, depending on the temperature and pH. Inorganic sulfur compounds can serve as energy sources for specialized prokaryotes and are important substrates for microbial growth in general. Here, we investigate dissimilatory sulfur cycling in the brine and sediments of a southwestern Siberian soda lake characterized by an extremely high pH and salinity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 82 publications
(106 reference statements)
3
82
0
Order By: Relevance
“…2C and 2D). This finding was unexpected because previous analysis of the occurrence of inorganic sulfur cycle genes in sequence genomes found that aprA occurs at higher frequencies than the other gene-encoding proteins required for dissimilatory sulfate-reduction genes (Vavourakis et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…2C and 2D). This finding was unexpected because previous analysis of the occurrence of inorganic sulfur cycle genes in sequence genomes found that aprA occurs at higher frequencies than the other gene-encoding proteins required for dissimilatory sulfate-reduction genes (Vavourakis et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the environmental conditions that select for dissimilatory sulfate-reduction gene families for a more frequent reliance on sulfate reduction remain unclear. In addition, metagenomics and metatranscriptomics, which avoid cultivation bottleneck, can characterize uncultivated microorganisms (Vavourakis et al, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Site-or habitat-speci c studies focus on spatiotemporal sampling of a single site or habitat of interest. The obtained genomes are then analyzed to elucidate how resident taxa mediate substrates turnover and elemental cycling, examine microbial interactions on the metabolic and cellular levels, and document how the community responds to natural and anthropogenic changes 1,2,3,4 . Function-based studies focus on genomes from single or multiple habitats to identify and characterize organisms involved in a speci c process, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Soda lakes are a type of saline lake with extremely high pH and salinity due to high concentrations of carbonate/bicarbonate and many other inorganic salts (1). Under alkaline and saline conditions, microbial activities are rather high, including surprisingly high biodiversity (2)(3)(4)(5), relatively high primary productivity rates (6)(7)(8)(9)(10), vigorous oxidation and reduction reactions of sulfur (11)(12)(13)(14)(15), and elevated biochemical cycling of various compounds and elements (16)(17)(18)(19). High concentrations of inorganic ions such as (bi)carbonate and phosphate provide adequate essential elements, while some saline environments, respectively (26).…”
Section: Introductionmentioning
confidence: 99%